PENGEMBANGAN INSTRUMEN EVALUASI PEMBELAJARAN IPA BERBASIS TAKSONOMI BLOOM - Popi Nita Rosdiana (Edulead : Journal of Education Management, 2021)
This study aims to develop an evaluation instrument for science learning in junior high school, considering that there are still some weaknesses in the instrument. The instrument model to be developed is a two-dimensional Bloom's taxonomy model. The method used in this research is the R & D (Research and Development) method or research and development method. The evaluation instruments developed in this study were description test questions, answer keys and scoring guidelines. The results of research and development of science evaluation instruments using Bloom's Taxonomy Two Dimensions the average value of the total validation given by the validator to the evaluation tool is 3.24, the evaluation instrument developed in the very valid category and the coefficient of validity of items from questions 1 to 30 have high validity criteria. The reliability coefficient of the description test questions developed was 1.019434 with a very high reliability category. Abstract Penelitian ini bertujuan untuk mengembangkan instrumen evaluasi pembelajaran IPA di SMP, mengingat masih ada beberapa kelemahan dalam instrumennya. Adapun model instrumen yang akan dikembangkan yaitu model taksonomi Bloom dua dimensi. Metode yang digunakan dalam penelitian ini adalah metode R & D (Research and Development) atau metode penelitian dan pengembangan. Instrumen evaluasi yang dikembangkan pada penelitian ini adalah soal tes uraian, kunci jawaban serta pedoman penskoran. Hasil penelitian dan pengembangan instrumen evaluasi pelajaran IPA dengan menggunakan Taksonomi Bloom Dua Dimensi nilai rata-rata total validasi yang diberikan oleh validator terhadap alat evalusi sebesar 3,24, instrumen evaluasi yang dikembangkan dalam kategori sangat valid dan koefisien validitas butir soal dari soal 1 sampai 30 memiliki kriteria validitas tinggi. Koefisien reliabilitas soal tes uraian yang dikembangkan sebesar 1,019434 dengan kategori reliabilitas sangat tinggi.